Assessing the Linkage Between Sustainability Reporting and Indonesia’s Firm Value: The Role of Firm Size and Leverage - Hardi, Irsan; Idroes, Ghalieb Mutig; Hardia, Natasha Athira Keisha; Fajri, Irfan; Furqan, Nurul; Noviandy, Teuku Rizky; Utami, Resty Tamara (Indatu Journal of Management and Accounting, 2023)
Sustainability reporting is widely regarded as an essential factor in enhancing a firm's value. In light of its importance, this study examines the impact of three sustainability reporting indicators - sustainability reporting disclosure, sustainability reporting index, and sustainability reporting score - on firm value, as well as determining the role of firm size and leverage. Utilizing a sample of 200 companies listed on the Indonesia Stock Exchange (IDX) during the research period from 2013 to 2021, the results of panel data regression reveal that two of the three indicators have a significant impact on firm value. Specifically, the sustainability reporting index exerts a positive impact, while the sustainability reporting score has a negative effect on firm value. Furthermore, path analysis estimations reveal that sustainability reporting mediates the positive relationship between firm size and firm value. This study's empirical findings underscore that sustainability reporting plays a pivotal role in shaping a firm's value, and these insights can be valuable for businesses and investors seeking to understand the financial implications associated with sustainability reporting.